Diagnosis of Students' Psychological Capital: Comparing the Adaptation of the English and Russian Questionnaires into the Kazakh Language (The Journal of Psychology and Sociology, 2026)
The study on the new phenomenon of "psychological capital" (PsyCap) is important and necessary in order to preserve the mental health of the student's personality and its sustainable development. This study adapts and validates the Russian version of the 2022 psychological capital questionnaire by V. Maralov, M. Kudak, and O. Smirnova and the English version "PsyCap-24", developed by F. Luthans, C.M. Youssef, and B.J. Avolio in 2007, into the Kazakh language. Personal development and professional potential depend on a person's self-efficacy, resilience, and optimism, which are determined by an individual's psychological capital. The purpose of the study is to adapt the "PsyCap" questionnaire into Kazakh by assessing the quality of adaptation and validation, comparing the English and Russian versions. The article presents the results of the adaptation and validation. The scientific and practical significance of the study lies in the expansion of empirical data on students' psychological capital, and the first data has obtained in Kazakhstan. The study has scientific and practical value and contributes to the development of psychodiagnostics in the country. 647 students (N = 647) from Al-Farabi Kazakh National University, Abai Kazakh National Pedagogical University, and South Kazakhstan Pedagogical Institute participated in the psychometric study on  the adaptation of the Russian-language version. This sample was randomly divided into two groups: N = 447 for exploratory factor analysis (EFA) and N = 200 for confirmatory factor analysis (CFA). A total of 115 students participated in the retest. The results show that the Russian-language version of the test by V. Maralov, M. Kudak, and O. Smirnova, in our translation and adaptation, has weak stability over time. The English-language version, adapted into Kazakh, is reliable and valid for measuring an individual's psychological capital. The practical significance of the results is obtaining a comprehensive picture of the levels of psychological capital of students in Kazakhstan. Overall, the results of the study demonstrate that the Kazakh version of the English-language PsyCap-24 test can be used as a valid instrument for assessing the psychological capital of students’ personalities.Keywords: psychological capital, self-efficacy, resilience, optimism, hope, psychodiagnostics, psychometrics